Impact of lameness and claw lesions in cows on health and production - Huxley, J.N. (Elsevier, 2013)
Lameness is one of the most important endemic diseases of cattle, particularly in the dairy sector. It has a significant impact on health and welfare and leads to a range of production losses. This article reviews the English language peer reviewed literature on the impacts of lameness in cattle on measures of health and production. There is a wealth of evidence from around the world demonstrating that lameness reduces milk yield. The extent of the reductions identified is difficult to summarise, however when losses have been calculated across a whole lactation, most are between 270 and 574kg. It is noteworthy that there is now strong evidence that lameness is a disease of high milk production i.e. high yielding animals are more likely to become lame. The impacts of lameness on nutrition and body condition appear complex. Overall the literature suggests that lameness leads to a reduction in the time spent feeding. A positive correlation between low body condition score and lameness has been demonstrated in a range of studies. Historically it was considered that lame cows lost weight as a consequence of the largely negative impacts of disease, on nutrition. Increasingly, evidence is appearing which suggests that the association between body condition score and lameness may in fact be the other way around i.e. high yielding cows which loose body condition during periods of negative energy balance become lame. The effect of lameness on fertility, measured in studies from around the world, is unequivocal. Lameness has substantial negative effects on fertility performance and reproductive parameters across a wide range of areas. Evidence on the association between lameness and culling is mixed. The majority of published work suggests that animals which suffer from lameness are more likely to be culled, although the converse has also been demonstrated. A review of the literature in this area demonstrates just how substantial the negative effects of lameness are on cattle health and production. The impacts are wide ranging and significant from both a welfare and an economic performance perspective. Further work is urgently required to control this important and prevalent condition.